NekNominate: Social Norms, Social Media, and Binge Drinking. Issue 5 (4th May 2017) - Wombacher, Kevin; Reno, Jenna E.; Veil, Shari R.
ABSTRACT: This study examines the social-media-based binge drinking game NekNominate and how this phenomenon is related to social norms. NekNominate is a game wherein players are nominated to film themselves "neking" or chugging copious amounts of alcohol or drinking alcohol in a novel or humorous manner. The player then nominates other players via social media who then have a specific timeframe in which they must complete their challenge or face ridicule. Health communication research on drinking behaviors has often looked at the role of social norms in determining these behaviors. News stories ( n = 44) of NekNominate and tweets ( n = 851) culled using the hashtag #NekNominate during three different time periods are analyzed to identify the normative forces at play in this recent phenomenon.